PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT (COMMUNITY BASED TOURISM) DI AIR TERJUN UBADARI, DISTRIK KRAMOMONGGA, KABUPATEN FAKFAK - Risma Niswati Tarman; James W.T Patanduk; Ahfandi Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The development of the tourism industry has not only impacted the country's foreign exchange income, but also expanded business opportunities, created new jobs for the unemployed, and made it possible to overcome regional unemployment. The purpose of this study was to find strategies to develop community-based tourism in Ubadari Falls and the factors that support and hinder the development of community-based tourism in Ubadari Falls. The type of research used is descriptive qualitative research, this type of research is phenomenological, and the data collection techniques used by researchers are interviews, documentation, and observations. The whistleblowers in this investigation are governments, businesses and communities. Primary and secondary data are used as data sources. The data analysis techniques used are qualitative data and the data validations used are extended study period, careful observation and triangulation..Keywords: Tourism Development, Community Based, Community Based Tourism